Emergency Tower System For An Accident - Muhammad Raihan Nurrizka; Erika Loniza; Taqwa Anggara Mukti; Oki Priyanto (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2023)
An emergency is an accident that cannot be predicted when it will happen. Emergency situation is a patient's clinical condition that need immediate medical action, to save lives and prevent further disability. campus is a place with high mobility of the academic community, so the potential for an emergency to occur in the campus area is quite large Apart from accidents, emergency cases that require prompt and appropriate treatment are sudden cardiac arrest. The life expectancy of cardiac arrest sufferers is very dependence on the competence of helpers to provide. Therefore, the process of handling emergency cases in the campus area can be carried out by developing a risk management ecosystem through an emergency tower that is integrated in the Detector Tower wirelessly. Emergency tower is a tower to provide information related to an emergency situation. This tower use an esp8266 as microcontroller to send information, sirins for an indicator to make an announcement there is an accident. Door lock to lock first aid box that only opens when push button got pressed. The result of emergency tower are can send alert information and do two-way communication with the Detector Tower, which can provide emergency handling through the Detector Tower installed at the location of the officer in charge. While waiting the Emergency tower is equipped with a first aid kit box that can be used as well as CCTV that will monitor events in the area. The emergency tower system has 100% that can help to handle emergency situation.